2018
DOI: 10.2337/dc18-0051
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Dose Glucagon as a Novel Approach to Prevent Exercise-Induced Hypoglycemia in Type 1 Diabetes

Abstract: MDG may be more effective than insulin reduction for preventing exercise-induced hypoglycemia and may result in less postintervention hyperglycemia than ingestion of carbohydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 25 publications
2
44
0
2
Order By: Relevance
“…clamp method could have avoided this bias [34]. Recently, results were published from a study in a similar group of individuals performing 45 min of exercise at four different sessions under conditions of: (1) no intervention; (2) 50% basal insulin reduction; (3) 40 g oral glucose tablets; or (4) after injections of 150 μg glucagon [15]. In contrast to our study, the investigators found that none of the participants receiving glucagon before exercise experienced hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…clamp method could have avoided this bias [34]. Recently, results were published from a study in a similar group of individuals performing 45 min of exercise at four different sessions under conditions of: (1) no intervention; (2) 50% basal insulin reduction; (3) 40 g oral glucose tablets; or (4) after injections of 150 μg glucagon [15]. In contrast to our study, the investigators found that none of the participants receiving glucagon before exercise experienced hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study found that an injection of 150 μg glucagon may be more effective than insulin reduction for preventing exercise-induced hypoglycaemia and may also result in less post-intervention hyperglycaemia (i.e. less time spent in hyperglycaemia and fewer hyperglycaemic episodes) than ingestion of carbohydrates [15]. Currently, the use of low doses of glucagon to manage mild hypoglycaemia is not recommended by official guidelines for type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mini dose glucagon has been proposed as a novel approach to prevent exercise-induced hypoglycemia in T1DM patients. This approach has been demonstrated by Michael et al [34]. In their study, 15 adults with T1DM were treated with continuous subcutaneous insulin infusion and exercised while fasting in the morning at about 25% VO 2 max for 45 minutes under the condition of no intervention (control), 50% basal insulin reduction, 40-g oral glucose tablets, or 150 μg subcutaneous glucagon (MDG).…”
Section: Mini Dose Glucagonmentioning
confidence: 99%
“…One option for further improvement might be dual‐hormone artificial pancreas (DHAP) systems which, in addition to insulin, use glucagon to counteract the effect of excessive insulin . The administration of mini‐doses of glucagon in a DHAP system has been shown to be more effective in preventing hypoglycaemia than the suspension of insulin delivery alone, particularly in situations of rapidly decreasing glucose levels, such as late postprandial hypoglycaemia or physical activity . As currently available glucagon formulations show limited stability, daily glucagon renewal is required, making the use of DHAP systems cumbersome .…”
Section: Introductionmentioning
confidence: 99%
“…delivery alone, particularly in situations of rapidly decreasing glucose levels, such as late postprandial hypoglycaemia or physical activity. [4][5][6][7][8][9] As currently available glucagon formulations show limited stability, daily glucagon renewal is required, making the use of DHAP systems cumbersome. [10][11][12] Because of this practical limitation, mainly shortterm efficacy and safety have been demonstrated to date.…”
mentioning
confidence: 99%